The effects of formulated palmitoylethanolamide supplementation on indicators of stress and heart rate variability in female university students: a randomised cross-over trial - Deb, Sanjoy K.; Kim, Nadia; Parolin, Brenda; Renshaw, Derek; Zariwala, Mohammed Gulrez (Frontiers in Nutrition, 2025)
BackgroundChronic stress is a prevalent issue among university students, negatively affecting both mental and physiological health. Palmitoylethanolamide (PEA), particularly in the Levagen+® formulation, has been investigated for its potential stress-modulating effects through its anti-inflammatory and neuroprotective properties. This study aimed to assess the effects of 6 weeks of Levagen+® PEA supplementation on physiological and subjective markers of stress in moderately stressed female university students.MethodsA double-blind, placebo-controlled crossover trial was conducted with 16 female participants who met the inclusion criteria based on the Perceived Stress Scale (PSS). Participants were randomly assigned to receive either 6 weeks of PEA supplementation (600 mg/day) or a placebo, with a six-week washout period. Stress responses were assessed through heart rate variability (HRV), subjective stress and mood measures (PSS, PANAS), and salivary cortisol levels. To enhance ecological validity, assessments were conducted in real-life settings rather than laboratory environments.ResultsPEA supplementation significantly increased the Standard Deviation of Normal-to-Normal (SDNN), a key HRV marker associated with autonomic resilience to stress (+9.70 ± 6.02 ms) compared to placebo (−5.72 ± 3.14 ms, p = 0.024), suggesting enhanced physiological stress regulation. While there was a trend of increased Root Mean Square Successive Difference (RMSSD) with PEA, it did not significantly change between conditions (p = 0.087). Similarly, a trend toward reduced self-reported stress was observed, though it did not reach statistical significance. No significant changes were detected in positive (p = 0.78) or negative (p = 0.95) emotions experienced. Salivary cortisol levels remained unchanged between conditions (p = 0.70).ConclusionThis exploratory study demonstrates for the first time that PEA supplementation may enhance physiological resilience to stress as indicated by improved HRV. While subjective stress and emotional measures did not show significant changes, the observed trend suggests potential benefits in individuals experiencing moderate stress. Given PEA’s role in the endocannabinoid system and its influence on inflammation, further research is warranted in larger and more diverse populations, including individuals with higher baseline stress levels. These preliminary findings contribute to the growing body of evidence supporting PEA as a promising dietary intervention for stress management.Clinical trial registrationhttps://clinicaltrials.gov, NCT06225440.